First Report of Occurrence of Rust in South Gujarat, India - Deshmukh, A. J.; Singh, Pushpendra; Prajapati, V. P.; Patel, Brijesh (International Journal of Economic Plants, 2018)
The incidence of rust (Uromyces sp.) on chickpea cv. GG-2 was first noticed during the rabi-2018 in south Gujarat, India. Symptoms were observed initially just after flowering stage on the lower leaves and consequently on upper leaves as small, round or oval, light brown to dark brown pustules, which coalesces later to form bigger pustules covering with a ring of small pustules under field conditions.The disease severity ranged from 24 to 30%. The urediospores were observed to be yellowish to brownish in colour. The shape of urediospores was observed as globose, echinulate, measuring 18-26 µm in diameter. Based on the symptomatology and morphological characters of the uredospores, the pathogen was identified as Uromyces sp. This is thought to be the first report of the pathogen causing chickpea rust from south Gujarat, India.